2022
DOI: 10.1101/2022.12.03.518987
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG is better left alone

Abstract: Automated preprocessing methods are critically needed to process the large publicly-available EEG databases, but the optimal approach remains unknown because we lack data quality metrics to compare them. Here, we designed a simple yet robust EEG data quality metric assessing the percentage of significant channels between two experimental conditions within a 100 ms post-stimulus time range. Because of volume conduction in EEG, given no noise, most brain-evoked related potentials (ERP) should be visible on every… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Within the reviewed papers, we found that many characteristics of phase-locked EEG signals are often only visible by averaging across multiple gaits, trials, and even subjects. The authors argue that these mean characteristics are “typical brain patterns” suited to be used as commands for BCI systems (Delorme, 2022 ). However, their high inter-subject and inter-trial variability shows that approaches based on averaged characteristic patterns might not help to build robust BCI systems (Kline et al, 2015 ; Nathan and Contreras-Vidal, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the reviewed papers, we found that many characteristics of phase-locked EEG signals are often only visible by averaging across multiple gaits, trials, and even subjects. The authors argue that these mean characteristics are “typical brain patterns” suited to be used as commands for BCI systems (Delorme, 2022 ). However, their high inter-subject and inter-trial variability shows that approaches based on averaged characteristic patterns might not help to build robust BCI systems (Kline et al, 2015 ; Nathan and Contreras-Vidal, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The field of EEG data analysis faces a significant challenge in separating non-neuronal motion artifacts from neuronal activity, as noted in several studies (Gwin et al, 2010 ; Snyder et al, 2015 ; Symeonidou et al, 2018 ; Delorme, 2022 ). The primary reason for this difficulty is the lack of a ground truth measurement of the pure brain signals, which makes it challenging to create and evaluate artifact removal methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…adaptive filtering (Mancini et al, 2015) and linear decomposition (Bai et al, 2016;Hernandez-Pavon et al, 2022), and so such methods might prove useful for reducing any potential artefacts introduced by fNMES. It should be noted however, that a liberal cleaning of EEG data can have minimal, and even detrimental effects, on the measurement of brain components (Delorme, 2022).…”
Section: Introductionmentioning
confidence: 99%